Kalinga a geriatric medical health and wellness center - Veridiano, Katrine Aira A.
Kalinga ; a geriatric medical health and wellness center is a study exploring the possibilities of promoting users' health by providing a supportive and therapeutic environment wherein patients, families and staff acquire positive effects from the designed environment. The creation of a therapeutic environment is guided by four major goals. These goals are mainly focused on reducing the environmental stressors, providing positive distractions, fostering social support among users and giving users a sense of control over the environment. This was achieved by utilizing different methods and treatments in the design in order to maximize the effects of the built environment in the psycho-social and physiological state of its users. Ease of use for the elderly is also one of the main focus of the design of the facility which eliminates environmental stressors and empowers the elderly to use the facility without having to depend much on others in using the facility.